U1 snRNP regulates cancer cell migration and invasion in vitro - Oh, Jung-Min; Venters, Christopher C.; Di, Chao; Pinto, Anna Maria; Wan, Lili; Younis, Ihab; Cai, Zhiqiang; Arai, Chie; So, Byung Ran; Duan, Jingqi; Dreyfuss, Gideon (Nature communications, 2020)
Stimulated cells and cancer cells have widespread shortening of mRNA 3’-untranslated regions (3’UTRs) and switches to shorter mRNA isoforms due to usage of more proximal polyadenylation signals (PASs) in introns and last exons. U1 snRNP (U1), vertebrates’ most abundant non-coding (spliceosomal) small nuclear RNA, silences proximal PASs and its inhibition with antisense morpholino oligonucleotides (U1 AMO) triggers widespread premature transcription termination and mRNA shortening. Here we show that low U1 AMO doses increase cancer cells’ migration and invasion in vitro by up to 500%, whereas U1 over-expression has the opposite effect. In addition to 3’UTR length, numerous transcriptome changes that could contribute to this phenotype are observed, including alternative splicing, and mRNA expression levels of proto-oncogenes and tumor suppressors. These findings reveal an unexpected role for U1 homeostasis (available U1 relative to transcription) in oncogenic and activated cell states, and suggest U1 as a potential target for their modulation. U1 snRNP is a key regulator of mRNA biogenesis through its roles in splicing, and transcription and 3’-end processing. Here the authors show a tumor suppressor-like function of U1 snRNP using in vitro cell migration/invasion assays and transcriptome profiling.